Nanotechnology In Medicine - Aditi Surve; Rutika Ithape; Akash Pandya; Prof. Akshata Badade (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Nanotechnology has risen as a promising field in medication, advertising the potential to revolutionize diagnostics, therapeutics, and imaging, with decreased side impacts, and made strides quiet results. Method for the research will be getting the research papers already existing, studying them and understanding their content and proceeding accordingly. Outcome was we found out that nanotechnology can be helpful in so many ways not just medicine but other fields too. Conclusion from the topic is as inquire about increments, different sorts of cross breed NPs appear progressed conveyance properties and get more consideration. Advance inquire about into the science of individual cancers will lead to more particular investigate headings for these drugs.